ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT MASYARAKAT MENABUNG DI BANK SYARIAH (Studi pada Masyarakat Desa Lajut Kecamatan Praya Tengah) - andre muzakkir; Yunia Ulfa Variana; Any Tsalasatul Fitriyah; Suriani (Jurnal Perbankan Syariah, 2022)
This study was conducted to find out: whether factor of trust, perception, knowledge and promotion influence partially and simultaneously on the interest of people saving in Islamic banks. This research is a quantitative study using primary data by providing questionnaires to the community in Lajut Village, Praya Tengah District, with a sample of 100 respondents. The analysis technique used is multiple regression analysis techniques. Based on the results of the hypothesis test, the results of partial research (t test) are confirmed (X1), perception (X2), and promotion (X4) have a significant and positive effect on community interest in saving in Islamic banks with a significance level of 0.028, 0.002 and 0.000 temporarily For the Knowledge Variable (X3) has no significant effect with a significance value of 0.356. The results of research simultaneously (test f) obtained a variable trust, perception, knowledge and promotion significantly influence public interest with a significance value of 0,000.